Precision medicine in pediatric sepsis - Atreya, Mihir R. (Curr Opin Pediatr, 2019)
PURPOSE OF REVIEW: Pediatric sepsis is a heterogeneous state associated with significant morbidity and mortality, but treatment strategies are limited. Clinical trials of immunomodulators in sepsis have shown no benefit, despite having a strong biological rationale. There is considerable interest in application of a precision medicine approach to pediatric sepsis to identify patients who are more likely to benefit from targeted therapeutic interventions. RECENT FINDINGS: Precision medicine requires a clear understanding of the molecular basis of disease. ‘Omics data’ and bioinformatics tools have enabled identification of endotypes of pediatric septic shock, with corresponding biological pathways. Further, using a multi-biomarker based approach, patients at highest risk of poor outcomes can be identified at disease onset. Enrichment strategies, both predictive and prognostic, may be used to optimize patient selection in clinical trials, and identify a sub-population in whom a therapy of interest may be trialed. A bedside to bench to bedside model may offer clinicians pragmatic tools to aid in decision making. SUMMARY: Precision medicine approaches may be used to sub-classify, risk-stratify, and select pediatric patients with sepsis who may benefit from new therapies. Application of precision medicine will require robust basic and translational research, rigorous clinical trials, and infrastructure to collect and analyze big data.